Supporting patients and families religious and spiritual needs in ICU can we do more? - TIMMINS, FIONA (My University, 2015)
For both families and patients, admission to the hospital environment can be frightening. This sense of fear is magnified in the intensive care unit (ICU) by the severe conditions and an intensive technological environment. While nurses grow accustomed to this, we know from first-hand experience that patients and families experience the ICU as a daunting and dehumanizing environment. In the ICU, patients’ identities change as they lose emotional intimacy (Plakas et al., 2009). ICUis also the place where many, perhaps for the first time, face their own mortality
PUBLISHED
Keywords: intensive care unit (ICU), spirituality; intensive care unit (ICU), spirituality